Inversion comique ou critique satirique ? La vue du Capitole de Hieronymus Cock (1562) - Ribouillault, Denis (RACAR : Revue d'art canadienne / Canadian Art Review, 2013)
Hieronymus Cock’s view of the Capitoline Hill, published in his 1562 series on Roman ruins, has long been considered a useful document by historians of art and architecture for the key historical and topographical information it contains on one of Rome’s most celebrated sites during the Renaissance. Beyond its documentary nature, which, as will appear, was essentially rhetorical, the view also offers much information as to how a mid-sixteenth-century Flemish artist might perceive Rome’s illustrious topography and celebrated ancient statuary. In other words, Cock’s engraving enables us to put into practice what may be called an “archaeology of the gaze.” Through previously unnoticed details, Cock invents a comical—verging on the satirical—vision of the antique sculptures proudly displayed on the famous piazza. Such an ironical reversal of Italian classical dignity is typical of the attitude of some contemporary Flemish artists, such as Pieter Bruegel the Elder, who was then close to Cock, and exposes the ambivalent position of some Northern European artists towards the classical tradition and Italian art theory. Finally, the analysis of other engravings of ruins by Hieronymus Cock where two emblematic characters—the draftsman and the kakker (the one who defecates)—appear side by side, sheds light on the origin and possible significance of these comical and subversive details.